2016
DOI: 10.1021/acsmacrolett.6b00538
|View full text |Cite
|
Sign up to set email alerts
|

Living Anionic Copolymerization of 1-(Alkylsulfonyl)aziridines to Form Poly(sulfonylaziridine) and Linear Poly(ethylenimine)

Abstract: The anionic ring-opening copolymerization of 1-(methylsulfonyl)aziridine (MsAz) and 1-(sec-butylsulfonyl)aziridine ( s BsAz) produces a soluble random copolymer P(MsAz-r-s BsAz), which can subsequently be converted to linear poly(ethylenimine) (lPEI). The copolymerization of MsAz and s BsAz is living and allows for the synthesis of copolymers with low molecular weight distributions. Sequential anionic polymerization of MsAz and s BsAz with 2-methyl-1-(methylsulfonyl)aziridine (MsMAz) creates P(MsAz-r-s BsAz)-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 28 publications
4
66
0
Order By: Relevance
“…The azaanionic polymerization of activated aziridines was recently established. [4][5][6][7][8][9] To enable anionic polymerization of aziridines, the acidic proton at the nitrogen needs to be substituted by an activating group, e.g. a sulfonamide group (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The azaanionic polymerization of activated aziridines was recently established. [4][5][6][7][8][9] To enable anionic polymerization of aziridines, the acidic proton at the nitrogen needs to be substituted by an activating group, e.g. a sulfonamide group (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that steric groups such as C‐10 chains or bulky phenyl groups do not hamper the polymerization . In addition, the electron withdrawing group, which is attached to the aziridine ring by a cleavable sulfonamide, can be used as a handle to control chemical function . The electron withdrawing behavior activates the aziridine and thereby influences the polymerization kinetics .…”
Section: Resultsmentioning
confidence: 97%
“…[22,25] In addition, the electron withdrawing group, which is attached to the aziridine ring by a cleavable sulfonamide, can be used as a handle to control chemical function. [18,26] The electron withdrawing behavior activates the aziridine and thereby influences the polymerization kinetics. [22] StMAz is estimated to have a similar electron withdrawing behavior as the TsMAz.…”
Section: Monomer Synthesismentioning
confidence: 99%
“…[38][39][40] The branching was minimized by Goethals et al using N-(2-tetrahydropyranyl)aziridine (THPA), which could be cleaved under mild conditions to obtain L-PEI. 41,42 The polymerization of activated sulfonamide aziridines via living anionic polymerization was recently explored by Bergman 43 and Wurm et al 42,44,4546 The obtained polyaziridines or polysulfonamide could partially (desulfonylated) to obtain L-PEI either via hydrolytic cleavage 47 or via reductive removal with a catalyst. 42 Scheme 3.…”
Section: Scheme 2 Schematic Representation Of the Ring Opening Polymmentioning
confidence: 99%